2020
DOI: 10.22271/chemi.2020.v8.i4aq.10187
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic variability, heritability and genetic advance for yield and its components in Pea (Pisum sativum L.)

Abstract: Genetic variability, heritability and genetic advance as percent over mean for nineteen quantitative traits of pea germplasms were assessed during rabi season 2017-2018 under Pea Improvement Project at Seed Breeding Farm, Department of Plant Breeding and Genetics, J.N.K.V.V., Jabalpur, (M.P.).High value of PCV and GCV was recorded high for number of pods per plant followed by number of effective nodes per plant, number of seeds per plant, number of nodes per plant. High heritability coupled with high genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…This variation in genotypes for all the traits may be a result of genotypic diversity, environmental effect and their interaction (G  E). Present results concur with the findings of (Barcchiya et al, 2018;Singh et al, 2019;Thapa et al, 2020). Genetic Variability, Correlation and Path Coefficient Analysis in Advanced Matromorphic Generations of Garden Pea (Pisum sativum L.)…”
Section: Resultssupporting
confidence: 91%
“…This variation in genotypes for all the traits may be a result of genotypic diversity, environmental effect and their interaction (G  E). Present results concur with the findings of (Barcchiya et al, 2018;Singh et al, 2019;Thapa et al, 2020). Genetic Variability, Correlation and Path Coefficient Analysis in Advanced Matromorphic Generations of Garden Pea (Pisum sativum L.)…”
Section: Resultssupporting
confidence: 91%
“…Aside from the differences in precipitation quantity and distribution, these features may also be influenced by the timing of sowing, according to Bozoglu et al (2007). The research conducted by Barcchiya et al (2018) and Saxesena et al (2014) suggests that SPP is mainly influenced by environmental factors rather than genotype, although it does exhibit significant heritability in a broader sense, while PL is a heritable trait, meaning that genetic factors, more than agroecological conditions, have a major influence on this trait (Avci and Ceyhan, 2006), which can be seen from similar results on two localities. By comparing Comparative Analysis of Agronomic Traits, Seed Color Variability and Protein Content in Pisum sativum L. Cultivars Across... the average of the two-year results at both locations, very small differences were observed in the TSW , which confirms that this trait is highly heritable and genetically determined (Burstin et al, 2015;Georgieva et al, 2016;Singh et al, 2017).…”
Section: Agroecological Impact On Pea Traitsmentioning
confidence: 62%
“…The low heritability estimates for seed yield and functional properties may indicate that the genetic variance is low or the error variance is large. Different studies reported moderate to high heritability estimates for seed yield and weight in pea (Afreen et al, 2017; Barcchiya et al, 2018; Georgieva et al, 2016; Meena et al, 2017; Singh & Dhall, 2018; Uhlarik et al, 2022; Yimam et al, 2020). Barcchiya et al (2018) and Uhlarik et al (2022) reported high heritability estimates for total protein in pea.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies reported moderate to high heritability estimates for seed yield and weight in pea (Afreen et al, 2017; Barcchiya et al, 2018; Georgieva et al, 2016; Meena et al, 2017; Singh & Dhall, 2018; Uhlarik et al, 2022; Yimam et al, 2020). Barcchiya et al (2018) and Uhlarik et al (2022) reported high heritability estimates for total protein in pea. Indeed, different studies estimated heritability using different methods, making direct comparison difficult.…”
Section: Discussionmentioning
confidence: 99%